PENGARUH PENGGUNAAN MADU TERHADAP NILAI pH, SINERESIS, DAN TOTAL BAKTERI ASAM LAKTAT YOGHURT SINBIOTIK - Baguna, Reynaldi; Yelnetty, A.; Siswosubroto, S.E.; Lontaan, N. (ZOOTEC, 2020)
THE EFFECT OF THE ADDITION OF HONEY TO THE PH VALUE, SYNERESIS AND TOTAL LACTIC ACID BACTERIA OF SINBIOTIK YOGURT. This study was conducted to determine whether honey gives an influence on the pH value, syneresis and LAB of synbiotic yogurt. In this study, the main ingredients used were 5 liters UHT milk, Skim milk 400 g, honey 240 mL, Lactobacillus acidophillus bacteria, Streptococcus thermophilus and Lactobacillus bulgaricus, aqudes, MRS Media (Man Rogosa Sharpe Medium). Equipment used during the study included autoclave, pH meter, Erlenmeyer, test tube, pipette, thermometer, analytical scale, petri dishe, desiccator, blender, oven, incubator, micro pipette, burette, spritus lamp, goblet, refrigerator. This research was carried out on January 7 2019 until March 12 2019 at the Laboratory of Animal Product Technology Faculty of Animal Husbandry, Sam Ratulangi University, Manado. The experimental design used in this study was a Completely Randomized Design (CRD) method with treatments 5 and 4 replications. The variables analyzed in this study are pH, Sinereis and Total LAB. The data obtained were analyzed using ANOVA, there were significant differences between the treatments followed by the BNJ test. The results of this study indicate that the treatments of P0(0%), P1(3%), P2(6%), P3(9%) and P4(12%) have a very significant effect (P <0.01) on the pH value, Sineresis and Total LAB. Based on the results and discussion that the use of honey by 12% can increase the value and produce the best pH, syneresis and total lactic acid bacteria in synbiotic yogurt.Keywords: Sinbiotic Yogurt, Honey, pH, Sinresis, LAB.